Some characteristics of job-seeking registered at the various employment offices in Peninsular Malaysia. - Toh , Kin Woon (Universiti Kebangsaan Malaysia, 1975)
This article attempts at studying the characteristics of the unemployed registered at the various Employment Offices in Peninsular Malaysia based on data for the year 1973. It has been found from the study that a greater majority of those unemployed registered with the Employment Offices are males between the ages of 15-24 who in the main are unskilled with no work experience and very poor educational backgrounds. They are mainly concentrated in the larger metropolitan centers where the rate of unemployment is high. It has also been found that less than half of the total number of unemployed in Peninsular Malaysia seek the assistance of the various Employment Offices in finding employment for them.